Factors influencing safe glucose-lowering in older adults with type 2 diabetes: A PeRsOn-centred ApproaCh To IndiVidualisEd (PROACTIVE) Glycemic Goals for older people A position statement of Primary Care Diabetes Europe - Hambling, C. E.; Khunti, K.; Cos, X.; Wens, J.; Martinez, L.; Topsever, R.; Del Prato, S.; Sinclair, A.; Schernthaner, G.; Rutten, G.; Seidu, S. (ELSEVIER SCI LTD, 2019)
Diabetes in later life is associated with a range of factors increasing the complexity of glycaemic management. This position statement, developed from an extensive literature review of the subject area, represents a consensus opinion of primary care clinicians and diabetes specialists. It highlights many challenges facing older people living with type 2 diabetes and aims to support primary care clinicians in advocating a comprehensive, holistic approach. It emphasises the importance of the wishes of the individual and their carers when determining glycaemic goals, as well as the need to balance intended benefits of treatment against the risk of adverse treatment effects. Its ultimate aim is to promote consistent high-quality care for older people with diabetes. (C) 2018 Published by Elsevier Ltd on behalf of Primary Care Diabetes Europe.
Keywords: Type 2 diabetes; Older people; Frailty; Hypoglycaemia; Glycaemic goals